Inverse Trignometric Functions

Asked by  | 3rd Sep, 2009, 05:35: PM

Expert Answer:

sin (sin-1(1/5) + cos-1(x)) = 1

(sin-1(1/5) + cos-1(x)) = sin-1(1)

sin-1(1/5) + cos-1(x) = /2

Now by using the property,

sin-1(x) + cos-1(x) =  /2

⇒ x = 1/5

Similarly try the second question.

In case of multiple questions within a query, please post each question individually and let us know where you are getting stuck so that we would be able to explain things better.

Answered by  | 5th Sep, 2009, 12:16: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.